The influence of female directors and institutional pressures on corporate social responsibility in family firms in Latin America - Isabel-María García-Sánchez; Lázaro Rodríguez-Ariza; María-del-Carmen Granada-Abarzuza (Journal of Risk and Financial Management, 2021)
This paper has two main aims. Firstly, we examine whether, given a critical mass of female board members, their presence has a different effect on the firm's CSR practices according to its family or non-family nature. We then consider whether the moderating role of the institutional environment in Latin America enhances the role of female directors in influencing the board's attitude towards CSR strategies. The results obtained-from a sample of 22,958 observations, corresponding to an unbalanced data panel of 5124 companies for the period 2010-2016-confirm our hypothesis and also highlight the existence of type I (organisational) and type II (institutional) compensation effects, which reduce or eliminate differences between family and non-family firms, whether or not they are located in Latin American countries.
Keywords: 330; corporate social responsibility; family firms; female directors; board of directors; gender; corporate governance